(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2022)
This study was aimed to analyze food consumption, physical activity, nutritional status, and work productivity of tea pickers at PT SMM Kepahiang Regency, Bengkulu Province, Indonesia during Covid-19 Pandemic. Cross sectional study design was applied, and 100 tea pickers were participated. The tea pickers and their family characteristics data was collected by in-person interviews. The physical activity data was collected by 24-hours activities recall questionnaire; food consumption (food habits, types, and amounts) data was collected by semi quantitative food frequency questionnaires and 24-hour food recalls method; meanwhile work productivity was determined by tea pickers’ income. The majority of the sample (57%) was intermediate adulthood, and ≥90% tea pickers were categorized as not poor. The types of serelia, animal food, vegetable and fruit that most commonly consumed were rice (21 times a week); eggs (2-3 times a week); kale, carrots, pumpkin and cabbage (1-2 times each week);bananas and papayas (1-2 times per week), respectively. Most of tea pickers had normal nutritional status (62%); moderate category of physical activity levels (84%) and moderate category of work productivity (80%). The protein consumption level and physical activity level were correlated significantly with nutritional status (p<0.05), meanwhile nutritional status was significantly correlated with work productivity (p<0.05).